The functions of gong ensemble music in death rituals of the Dusun Tatana / Ashley Saleviter - Saleviter, Ashley Saleviter (Faculty of Music, 2016)
This study explores the gong ensemble music and its functions in death rituals of the Dusun Tatana of Kuala Penyu, Sabah. The Surabai is a gong ensemble music of the Dusun Tatana that is used in death rituals of the ethnic and can only be played when there is death happened in a Dusun Tatana Village. There is a chronological order in-which the Surabai needs to be played. This study also explains about the relation of the Tungkas Moginum with the death rituals of the Dusun Tatana. This provides insights to how festive repertoires also integrated in death rituals in the Dusun Tatana Customs. Lastly, this study will also explains the characteristics of the Surabai and the Tungkas Moginum and the differences they have in terms of rhythmic and melodic aspects to show how their prominence in rituals and festive occasions affects their musical aspect in a death ritual.